2016
DOI: 10.1016/j.socscimed.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Does income relate to health due to psychosocial or material factors? Consistent support for the psychosocial hypothesis requires operationalization with income rank not the Yitzhaki Index

Abstract: Research on why income influences health has produced mixed findings. Many, but not all, studies suggest that the relationship between income and health is due to income indicating psychosocial position rather than the associated material benefits. The inconsistent findings may be partly due to the use of the Yitzhaki Index, a function which calculates the accumulated income shortfall for an individual relative to those with higher income, in order to represent the psychosocial position conferred by income. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Psychosocial factors along with materialist explanations are the primary hypotheses to explain the association between SES, typically measured by income, and health outcomes. Materialist explanations focus on lack of material resources leading to poorer health, while psychosocial explanations emphasize lower income being associated with negative comparisons with higher social status and associated stress and ill health . However, the material and psychosocial approaches are not contradictory and can be considered as complementary in providing a more comprehensive picture of health inequalities with the potential to explain unaccounted variance in each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial factors along with materialist explanations are the primary hypotheses to explain the association between SES, typically measured by income, and health outcomes. Materialist explanations focus on lack of material resources leading to poorer health, while psychosocial explanations emphasize lower income being associated with negative comparisons with higher social status and associated stress and ill health . However, the material and psychosocial approaches are not contradictory and can be considered as complementary in providing a more comprehensive picture of health inequalities with the potential to explain unaccounted variance in each other.…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 2 Unadjusted and adjusted (block entry and full model) associations of socioeconomic, demographic, psychosocial and health behaviour explanatory variables by the outcome of mean EQ-5D scores emphasize lower income being associated with negative comparisons with higher social status and associated stress and ill health. 29 However, the material and psychosocial approaches are not contradictory and can be considered as complementary in providing a more comprehensive picture of health inequalities with the potential to explain unaccounted variance in each other. While materialist views can include psychosocial aspects such as job control, a psychosocial approach tends to focus on proximal processes covering behavioural and psychological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the English Longitudinal Study of Ageing (ELSA) and the Longitudinal Internet Studies for the Social Sciences (LISS), Hounkpatin et al (2016) found that Income Rank was a stronger and more consistent predictor of self-rated and objective health (allostatic load) when compared with other measures, such as the Yitzhaki Index, using model fit statistics ( BIC and AIC ). In this study population, Income Rank was more strongly correlated with depressive symptoms in Models 1 to 3 than the Yitzhaki Index when judged by −2LogL and Akaike Information Criterion ( AIC ).…”
Section: Discussionmentioning
confidence: 99%
“…In non-human primate societies there is no such thing as “income”; nonetheless, positional rank determines access to food, reproductive mates, and longevity. In human populations, lower Income Rank has been shown to correlate with worse self-rated health, allostatic load, obesity, mental distress, and suicidal ideation and attempts (Daly et al, 2015; Hounkpatin et al, 2016; Wetherall et al, 2015; Wood et al, 2012). It was also suggested that Income Rank might be a stronger and more consistent predictor of health when compared with other measures, such as the Yitzhaki Index (Hounkpatin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A large literature suggests that economic well-being shapes health behaviors (Pampel, Krueger, & Denney, 2010), access to quality health care (Centers for Disease Control and Prevention, 2013), and differential exposure to health hazards (Evans & Kim, 2010). In addition, much research suggests that inequality itself impacts health, where one's relative status vis-à-vis the economic distribution can shape health through greater chronic stress, exacerbating allostatic load (Hounkpatin, Wood, & Dunn, 2016). As a result, health limitations are more common among racial and ethnic minorities, those with low educational attainment, those in poverty, the unemployed, and the unmarried (e.g., Adler & Rehkopf, 2008;Blackwell, Villarroel, & Clarke, 2015;Liu & Umberson, 2008;Morello-Frosch, Zuk, Jerrett, Shamasunder, & Kyle, 2011).…”
Section: Individual Consequences Of Health Limitationsmentioning
confidence: 99%